Durability Optimization of Fiber Grating Hydrogen Sensor Based on Residual Stress - Wenbo Ma; Yuyang Li; Ning Yang; Li Fan; Yanli Chen; Xuan Zhou; Jiaping Li; Caiqian Yang (Sensors, 2021)
In this paper, in order to improve the durability of optical fiber grating hydrogen sensors, an optical fiber grating hydrogen sensor with high precision, stability, and durability is prepared. Based on the simplified two-dimensional model and finite element analysis, the effects of film thickness, coating speed, and coating times on the residual Mises equivalent stress between the sensor film and substrate were studied, and the optimum coating parameters were determined. The finite element analysis results show that the residual equivalent stress between the film and the substrate increases with the increase in the film thickness between 50 and 150 nm. The range of 200–250 nm is relatively stable, and the value is small. The coating speed has almost no effect on the residual equivalent stress. When the thickness of the film is 200 nm, the residual equivalent stress decreases with the increase in coating times, and the equivalent force is the lowest when the film is coated three times. The best coating parameters are the thickness of 200 nm, the speed of 62.5 μm/s, and the times of coating three times. The results of finite element analysis are verified by the hydrogen sensitivity test and durability test.